Biologics and chronic obstructive pulmonary diseases - Pavord, I (Elsevier, 2018)
The presence of airway inflammation in patients with chronic obstructive pulmonary disease (COPD) provides a rationale for biological agents targeting specific inflammatory pathways. This approach has been strikingly effective in patients with other chronic inflammatory diseases, such as rheumatoid arthritis, psoriasis, and asthma. However, there are important and unresolved challenges in COPD, including our incomplete understanding of heterogeneity of the lower airway inflammatory response and how these contribute to the clinical expression of disease. As a result, progress has been slow, and there have been many failures. One notable exception is the targeting of eosinophilic airway inflammation with anti-IL-5, which has an acknowledged and important role in the treatment of severe eosinophilic asthma. Recent phase III studies have shown a reduction in exacerbations of around 20% in patients with COPD and clear evidence of a blood eosinophil count-dependent beneficial effect. The demonstration of clinical efficacy linked to a clinically accessible biomarker raises the possibility of precision biomarker-directed use of biological agents in patients with COPD. The hope is that this will be an exemplar for the future development of biological agents in patients with COPD.